Advanced Intraprocedural Image Guidance for Endovascular Aortic and Branch-Vessel Procedures Using the Intraoperative Positioning System (IOPS) - Farivar, Behzad S. (Seminars in Interventional Radiology, 2024)
Endovascular aortic repair has transformed the treatment of aortic pathologies, providing minimally invasive alternatives to traditional open surgery. Despite these advancements, endovascular procedures continue to encounter substantial challenges, including navigating tortuous and calcified vessels, precise catheterization of the aortic branch vessels in complex cases, and the significant risks of radiation exposure to both patients and operators. Recent innovations in electromagnetic (EM) tracking and 3D imaging offer a promising alternative to traditional methods. This review focuses on the Intraoperative Positioning System (IOPS), a novel EM-based image guidance system developed by Centerline Biomedical, Inc. (Cleveland, OH). IOPS uses sensorized, EM-tracked devices to enhance procedural precision and safety by minimizing reliance on ionizing radiation while improving visualization and the accuracy of catheterization in vascular anatomies. This technology enables parts of the procedure to be performed without the need for ionizing radiation, offering a safer and more efficient approach to endovascular procedures.
Keywords: endograft; aneurysm; open repair; navigation; technology